Dance performance as a method of intervention as experienced by older persons with dementia. (24th June 2011) - Ravelin, Teija; Isola, Arja; Kylmä, Jari
<x xml:space="preserve">Abstract</x> Background. Previous studies have shown that dance can bring out the strength and resources of persons with dementia. Purpose. To describe for later evaluation how older persons with dementia experience dance performances in a nursing home. Design. Four dance performances, based on the recollections the older persons had of different seasons, were arranged in one nursing home. Methods. Qualitative descriptive study, with 13 older persons with dementia, four family members, seven nurses and three practical nurse students. Data were collected and analysed using methodological triangulation. Results. Older persons identified dance performance activity as a process. They had a positive attitude towards the dance performance and performers, and they had experiences of different elements of the dance performance. The older persons forgot their ailments during the performances, and the performances evoked various emotions and awoke memories. Some of them had negative experiences of dancing and dance performances. The older persons experienced a common bond with other spectators. Conclusion. Watching a dance performance is an active process for older persons with dementia. Implications for practice. Reminiscence about the dance performance gives the older person an opportunity to deal with the experiences evoked by the performance.